2017
DOI: 10.1007/s11356-017-9135-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a ternary Ag/RGO/ZnO nanocomposite via microwave irradiation and its application for the degradation of Rhodamine B under visible light

Abstract: Reduced graphene oxide supporting plasmonic photocatalyst (Ag) on ZnO has been synthesized via a facile two-step microwave synthesis using RGO/ZnO and AgNO. First step involves fabrication of RGO/ZnO via microwave irradiation. The nanocomposites were characterized by X-ray diffraction analysis, transmission electron microscopy, Fourier transform infrared spectroscopy, and Raman spectroscopy. Ag/RGO/ZnO shows enhanced photoactivity under visible light for the degradation of Rhodamine B. Enhanced charge separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Similar results were obtained by Mohit et al, [23] who found that the integration of Ag and rGO together reduces the E g value of ZnO from 3.19 eV to 2.9 eV. Furthermore, our values are consistent with those reported by Divya et al, [49] who have found that the E g of ZnO decreases from 3.14 eV to 2.62 eV, which is attributed to the synergetic interaction with Ag and rGO contents.…”
Section: Optical Propertiessupporting
confidence: 92%
“…Similar results were obtained by Mohit et al, [23] who found that the integration of Ag and rGO together reduces the E g value of ZnO from 3.19 eV to 2.9 eV. Furthermore, our values are consistent with those reported by Divya et al, [49] who have found that the E g of ZnO decreases from 3.14 eV to 2.62 eV, which is attributed to the synergetic interaction with Ag and rGO contents.…”
Section: Optical Propertiessupporting
confidence: 92%
“…For that reason, they are considered more toxic than the anionic ones. There are several methods to eliminate this pollutant, 62,63 but Zhao and co-workers 64 reported a new one where the porphyrin-based porous organic polymer H 2 5 (Fig. 3) is used as a photocatalyst for the degradation of RhB and also methylene blue (MB).…”
Section: Wastewater Treatment Using Polymeric Porphyrins or Porphyrin...mentioning
confidence: 99%
“…Genotoxicity may ascend via indirect mechanisms where NPs do not physically interrelate with the DNA molecule but with other "cellular components", such as those involved in the cell division process. Other cellular responses may be induced and give rise to genotoxicity, such as oxidative stress induction, inflammatory response, and aberrant signaling responses (34,19,21).The literatures on the toxicity of ZnONPs have focused on early developmental stages or on acute exposure to aquatic biomass (14). It is well known that, "Vitamins E and C are potent antioxidants and act by scavenging the free radicals or ROS and compensate the decrease in reduced glutathione" (38).…”
Section: Introductionmentioning
confidence: 99%